2021
DOI: 10.5194/amt-14-5555-2021
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer water vapour statistics from high-spatial-resolution spaceborne imaging spectroscopy

Abstract: Abstract. Daytime clear-sky total column water vapour (TCWV) is commonly retrieved from visible and shortwave infrared reflectance (VSWIR) measurements, and modern missions such as the upcoming Earth Surface Mineral Dust Source Investigation (EMIT) offer unprecedented horizontal resolution of order 30–80 m. We provide evidence that for convective planetary boundary layers (PBLs), spatial variability in TCWV corresponds to variability in PBL water vapour. Using an observing system simulation experiment (OSSE) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…We use q and cloud water (q c ) output from the five LES runs of shallow convection as in Richardson et al (2021a), with four cloudy cases (ARM, ARM_lsconv, BOMEX, RICO) and one case in which clouds do not form (DRY). Simulations use two models, EULAG for the ARM cases (Prusa et al, 2008) and JPL-UCONN LES for the others (Matheou and Chung, 2014).…”
Section: Large Eddy Simulation Outputmentioning
confidence: 99%
See 4 more Smart Citations
“…We use q and cloud water (q c ) output from the five LES runs of shallow convection as in Richardson et al (2021a), with four cloudy cases (ARM, ARM_lsconv, BOMEX, RICO) and one case in which clouds do not form (DRY). Simulations use two models, EULAG for the ARM cases (Prusa et al, 2008) and JPL-UCONN LES for the others (Matheou and Chung, 2014).…”
Section: Large Eddy Simulation Outputmentioning
confidence: 99%
“…Simulations use two models, EULAG for the ARM cases (Prusa et al, 2008) and JPL-UCONN LES for the others (Matheou and Chung, 2014). Simulation set-ups are described in Richardson et al (2021a) and the associated references (Brown et al, 2002;Kurowski et al, 2020;Matheou and Chung, 2014;Siebesma et al, 2003;vanZanten et al, 2011), and while some simulations represent oceanic boundary layers, we simply assume a land surface for the retrievals. Static reanalysis profiles from MERRA-2 (Gelaro et al, 2017) are appended above the LES domain, but the LES domains were shown to capture horizontal variability in q from analysis of LES output and airborne lidar profiles over the Pacific (Bedka et al, 2021).…”
Section: Large Eddy Simulation Outputmentioning
confidence: 99%
See 3 more Smart Citations